If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = -72 + 8x Reorder the terms: 12 + 4x = -72 + 8x Solving 12 + 4x = -72 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 12 + 4x + -8x = -72 + 8x + -8x Combine like terms: 4x + -8x = -4x 12 + -4x = -72 + 8x + -8x Combine like terms: 8x + -8x = 0 12 + -4x = -72 + 0 12 + -4x = -72 Add '-12' to each side of the equation. 12 + -12 + -4x = -72 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = -72 + -12 -4x = -72 + -12 Combine like terms: -72 + -12 = -84 -4x = -84 Divide each side by '-4'. x = 21 Simplifying x = 21
| -g=2.5g-(-3) | | 56x-4x=45 | | x^3-5x^2+5x-1=0 | | 3(0)+7y=21 | | 6x^2-42=0 | | 3x+7(0)=21 | | 2x+24=11x+84 | | 3x-12=11x-42 | | 17-x=11 | | 0=16(x^2)-7x-150 | | 4a+3=23 | | 12y-4=7 | | 5v^2-140=0 | | y(y+6)=0 | | 1+6y=6 | | 5x^2-26x=0 | | 2c^2-52c-54=0 | | a^2+16=0 | | 3x+132=12x-12 | | 4d+1-6D=3(5-3d) | | 3x+(-15)=-7 | | 3x+12=5x+4 | | 73x+12=5x+4 | | 2a+5+4a+9+3a= | | 5x+14+31=4x+73 | | 2a+5+4a+3a= | | x^2+3x+7=6 | | 9-9x=40-16x | | 3(9c-1)-4=25c+3 | | 0-4x=12-7x# | | 6x+3y=73 | | 8x-10=38 |